Effectiveness Environmental Change Learning Tools Based on STEM-PjBL Towards Students’ Collaboration and Communications Skills - Triana, Dwita; Ulung Anggraito, Yustinus; Ridlo, Saiful (Universitas Negeri Semarang, 2020)
Collaboration and communication are 21st century skills that must have everyone. Therefore, learning needs to be designed that is able to equip students with these skills to be able to continue to develop themselves in the 21st century. This study aims to analyze the effectiveness of environmental change learning tools based on STEM-PJBL for student collaboration and communication skills. The STEM-PjBL learning tools used include syllabus, lesson plans, teaching materials, student worksheets and evaluation tools. This research was conducted at SMA Negeri 4 Medan and SMA Negeri 16 Medan. The sample was taken using a purposive sampling method with a total sample of 126 students consisting of 4 classes. This research uses quantitative research methods with one group pretest-posttest design. Based on the results of the study showed the collaboration skills of students gained an average score of 0.817 with a very good category. Meanwhile students' communication skills gained an average score of 0.830 in the excellent category. This shows that STEM-PjBL-based environmental change learning tools are effective for student collaboration and communication skills.